Electroporation Enhances Bleomycin Efficacy in Cats with Periocular Carcinoma and Advanced Squamous Cell Carcinoma of the Head. (20th July 2015) - Spugnini, E.P.; Pizzuto, M.; Filipponi, M.; Romani, L.; Vincenzi, B.; Menicagli, F.; Lanza, A.; De Girolamo, R.; Lomonaco, R.; Fanciulli, M.; Spriano, G.; Baldi, A.
<x xml:space="preserve">Abstract</x> Background Advanced carcinoma of the head represents a substantial health problem in cats for local control and overall survival. Objectives Evaluate the capability of electrochemotherapy (ECT) to improve bleomycin efficacy in cats with periocular carcinoma and advanced carcinoma of the head. Animals Twenty‐one cats with periocular carcinoma (17 squamous cell carcinoma [SCC] and 4 anaplastic carcinoma) and 26 cats with advanced SCC of the head. Methods Nonrandomized prospective controlled study. Periocular carcinoma cohorts: 12 cats were treated with bleomycin (15 mg/m2 IV) coupled with ECT under anesthesia; 9 cats were treated with bleomycin alone. Advanced head SCC cohorts: 14 cats were treated with bleomycin (15 mg/m2 IV) coupled with ECT administered under sedation; 12 control cats were treated with bleomycin alone. ECT treatments (2–8) were performed every other week until complete remission (CR) or tumor progression occurred. Results Toxicities were minimal and mostly treated symptomatically. Overall response rate in the ECT treated animals was 89% (21 Complete Response [CR] and 2 Partial Response [PR]) whereas controls had response rate of 33% (4 CR and 3 PR). Median time to progression in ECT group was 30.5 months, whereas in controls it was 3.9 months (P < .0001). Median time to progression for ECT cohorts was 24.2 months for periocular cohort and 20.6 in advanced head SCC cohort, respectively. Conclusions Electrochemotherapy is well tolerated for advanced SCC of the head in cats; its use may be considered among loco‐regional strategies for cancer therapy in sensitive body regions such as periocular region.